Commonwealth guide to trading with NAFTA countries : practical information for business (Commonwealth Secretariat LondonGB, 1995)
Assists Commonwealth based companies to export successfully to North America. Provides essential information to exporters about the new trading environment. Contains detailed product and market information on fifteen important product groups.
DC